The PRMT5 inhibitor EPZ015666 is effective against HTLV-1-transformed T-cell lines in vitro and in vivo - Ernzen, Kyle; Melvin, Corrine; Yu, Lianbo; Phelps, Cameron; Niewiesk, Stefan; Green, Patrick L.; Panfil, Amanda R. (Frontiers in Microbiology, 2023)
Human T-cell leukemia virus type 1 (HTLV-1) is the infectious cause of adult T-cell leukemia/lymphoma (ATL), an extremely aggressive and fatal malignancy of CD4+ T-cells. Due to the chemotherapy-resistance of ATL and the absence of long-term therapy regimens currently available for ATL patients, there is an urgent need to characterize novel therapeutic targets against this disease. Protein arginine methyltransferase 5 (PRMT5) is a type II PRMT enzyme that is directly involved in the pathogenesis of multiple different lymphomas through the transcriptional regulation of relevant oncogenes. Recently, our group identified that PRMT5 is overexpressed in HTLV-1-transformed T-cell lines, during the HTLV-1-mediated T-cell immortalization process, and in ATL patient samples. The objective of this study was to determine the importance of PRMT5 on HTLV-1 infected cell viability, T-cell transformation, and ultimately disease induction. Inhibition of PRMT5 enzymatic activity with a commercially available small molecule inhibitor (EPZ015666) resulted in selective in vitro toxicity of actively proliferating and transformed T-cells. EPZ015666-treatment resulted in a dose-dependent increase in apoptosis in HTLV-1-transformed and ATL-derived cell lines compared to uninfected Jurkat T-cells. Using a co-culture model of infection and immortalization, we found that EPZ015666 is capable of blocking HTLV-1-mediated T-cell immortalization in vitro, indicating that PRMT5 enzymatic activity is essential for the HTLV-1 T-cell transformation process. Administration of EPZ015666 in both NSG xenograft and HTLV-1-infected humanized immune system (HIS) mice significantly improved survival outcomes. The cumulative findings of this study demonstrate that the epigenetic regulator PRMT5 is critical for the survival, transformation, and pathogenesis of HTLV-1, illustrating the value of this cellular enzyme as a potential therapeutic target for the treatment of ATL.